PENGARUH PROMOSI DAN BRAND TRUST TERHADAP MINAT BELI KONSUMEN PADA GALERI ELZATTA DI BALIKPAPAN - Suwandi Putra Durahman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims: (i) to find out the promotion and brand trust variables simultaneously have a significant effect on purchase intention (ii) to find out the promotion and brand trust variables partially have a significant effect on purchase intention (iii) to find out between the promotion and brand trust variables that most influence on consumer purchase intention at Elzatta Gallery in Balikpapan. This study uses three variables namely the promotion, brand trust and purchase intention. This type of research is a correlation method with a quantitative approach. The population in this research were all consumers of the Elzatta Gallery in Balikpapan whose exact number was unknown and the sampling technique used non-probability sampling with accidental sampling method, the number of samples was 100 respondents. Data collection techniques: field research (observation, interviews, questionnaires, documentation) and library research. Then the analysis technique used is multiple linear regression using the test: validity test, reliability test, classic assumption test (normality test, multicollinearity, heteroscedasticity), hypothesis test (partial, simultaneous, dominant), multiple linear regression analysis. The result obtained in this study are (i) Promotion and Brand Trust simultaneously had a significant effect on Purchase Intention (ii) Promotion and Brand Trust partially had a significant effect on Purchase intention (iii) Brand Trust is a variable that has the most influence on consumer purchase intention at Elzatta Gallery in Balikpapan.